Prioritizing of Risk Components in the perishable goods supply chain and Supplier selection in supply chain risk management - Gencay Karakayaa, Shahryar Ghorbani (International Journal of Advanced Science and Technology, 2020)
Presently, the topics of supply chain risk management and supplier selection have become one of the most important issues in the world and many studies have been done on such topic. The members of a supply chain are trying to respond to the market demand by choosing the best supplier. On the other hand, there is undeniable risk in the supply chain, and members of a chain tend to identify and prioritize these risks in order to be able to react quickly to prevent potential risks. The issue of identifying risk and choosing the best supplier in a perishable goods supply chain is important due to the short life of these and choosing an incorrect strategy for selecting supplier may impose irreparable damage to organizations.